Micropropagation of Rudbeckia hirta L. from seedling explants - P. Szarvas; A. Zsila-André; Z. Kováts; M. G. Fári (International Journal of Horticultural Science, 2005)
We conducted experiments for developing an in vitro micropropagation protocol starting from meristems of Rudbeckia hirta L seedlings. We pre-soaked the seeds in sterile ion-exchanged water for 17 hours, and then achieved surface disinfection in two separate steps. First, we used concentrated household sodium-hypochloride solution for 20 minutes and, also for 20 minutes, we applied hydrogen peroxide of 10%, which was followed by washing with sterile ion-exchanged water three times. For the propagation of seedling meristems, the combination of half-strenght solid Murashige and Skoog (1962) culture medium containing 10 mg/1 of kinetin or 2 mg/I of kinetin + 0.1 mg/1 of 2iP proved to be the most suitable. The average number of shoot-buds developed from the seedling axillary meristem in the best culture media varied between 5 and 17. Without separating them, we inoculated the shoot-bud clusters on MS culture medium containing 2 mg/1 of IAA. After four weeks of incubation we obtained elongated shoots which we separated and inoculated into a new culture medium and we obtained elongated roots. The rooted plants were gradually acclimatised in the cultivation room, potted and carried to a greenhouse, and then planted in open field for subsequent observation. By adopting this method, our laboratory started the micropropagation of the superior and/or elite genotypes of the Rudbeckia hirta L. being of special value in respect of breeding.